DEIXIS AND SPEECH ACT ON PRESIDENTIAL DEBATE BETWEEN DONALD TRUMP AND JOE BIDEN - Doamad Tastier; Oom Rohmah (Universitas Indraprasta PGRI, 2022)
This research is to analyze deixis and speech act on presidential debate between Donald Trump and Joe Biden. The research data is the final presidential debate between Donald Trump and Joe Biden on 20th October 2020. The research is qualitative research. Data are taken from the video downloaded from www. Youtube.com. The video is then transcribed and analyzed. The main research instrument is the researcher himself. Deixis found in this research are person deixis (74,88%), spatial deixis (5,55%), temporal deixis (2,19%), social deixis (13,55%), and discourse deixis (3,84%). The context in which deixis used are person deixis in which deictic expression indicates person reference, as first person, second person and third person. Then spatial deixis is in context that deictic expression indicates proximal place and distal place. Temporal deixis in in context in which deictic expression indicates time point. Social deixis is used in context to indicates the social rank of reference. Meanwhile, discourse deixis is used to refer to portion of unfolding discourse in which utterance is located. Speech acts found in the research are assertive (59,54%), directive (11,45%), commissive (16,79%), and expressive (12,21%). The kind of assertive found are informing, convincing, stating, claiming. The kind of directive consist of requesting, suggesting, and ordering. The kind of commissive consist of threatening and promising. The kind of expressive consist of greeting, apologizing, thanking, and surprising. The possible perlocutionary act found is that assertive, which are informing, convincing, and claiming, is Trump and Biden want to inform some facts related to the issues being discussed. Further they want to convince the voters to vote one of them to be next president of the United States of America. Claiming acts is to show about what Trump and Biden have done for America. Each of them claims that he is the better person for the next president. Commissive also is dominant illocutionary acts, particularly promising acts. This is because they are debating for the president.